One-way quantum computation with four-dimensional photonic qudits - JOO,J; KNIGHT,P; O'BRIEN,J; Rudolph,T (Physical Review A, 2007)
We consider the possibility of performing linear optical quantum computations making use of extra photonic degrees of freedom. In particular, we focus on the case where we use photons as quadbits, four-dimensional photonic qudits. The basic 2-quadbit cluster state is a hyperentangled state across polarization and two spatial mode degrees of freedom. We examine the nondeterministic methods whereby such states can be created from single photons and/or Bell pairs and then give some mechanisms for performing higher-dimensional fusion gates.